What is the right profile for getting a job? A stated choice experiment of the recruitment process - Stefan Eriksson; Per Johansson; Sophie Langenskiöld (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
We study the recruitment behavior of Swedish employers using data from a stated choice experiment. In the experiment, the employers are first asked to describe an employee who recently and voluntarily left the firm, and then to choose between two hypothetical applicants to invite to a job interview or to hire as a replacement for their previous employee. The two applicants differ with respect to characteristics such as gender, age, education, experience, ethnicity, religious beliefs, family situation, weight, and health. Our results show that employers discriminate against applicants who are old, non-European, Muslim, Jewish, obese, have several children, or have a history of sickness absence. Moreover, increasing the firms' cost of uncertainty in hiring - through more firm co-payment in the sickness benefit system - may reduce hiring, but does not affect the degree of discrimination. Also, there are only small differences in the degree of discrimination between different types of recruiters and firms. Overall, our results suggest that the discrimination, at least partially, should reflect statistical discrimination.
Keywords: J71; 330; Stated choice experiment; Discrimination; Gender; Age; Ethnicity; Obesity; Sickness absence; Arbeitsnachfrage; Personalbeschaffung; Arbeitsmarktdiskriminierung; Test; Schweden